Consumer electronics [Technology 2000 analysis and forecast]. - Perry, T.S (IEEE spectrum)
Most 20th-Century consumer electronic products have evolved predictably. A new technology proved feasible, a standard was set for it, and high-priced products were rolled out and snapped up by the ever-eager early adopter. Then, as production ramped up, prices dropped and the product became a mass-market item. This happened for television, radio, and audio compact disks. But that may not be the case in the 2lst century. Products launched in 1999 went from announcement to mass-market rollout in nearly the blink of an eye, issues like standards and copyrights have been left to be settled in their wake. The first 2lst-century product to follow this model was the downloadable digital audio player. These portable MP3 players, so called because they use the compression technology specified in Layer 3 of the MPEG-2 standard, are used to store downloaded digital music files from the Internet, and then play them back off line. Other developments include security, hard disk recorders, videogames, digital cameras, and digital TV